Tourism Sector Development Strategy in Lebong Regency Pad Improvement - Reno Oktapian; Ahmad Soleh; Rahman Febliansa (Penerbit Jurnal Indonesia, 2023)
The research objective was to determine the marketing strategy of tourism objects in Lebong Regency. The sample in this study were 6 employees at the Lebong Regency Tourism Office who were in charge of marketing tourism in Lebong Regency for internal factors and for external factors, namely visitors or tourists of white water natural attractions in Lebong Regency as many as 30 people, so that the total sample used in this study There were 36 people. The analytical method used was SWOT analysis which consisted of an Internal Strategic Factor Matrix (IFAS) and an External Strategic Factor Matrix (EFAS). The results of research on tourism marketing strategies in Lebong Regency, obtained several conclusions, namely the white water nature tourism marketing strategy in Lebong Regency supports aggressive strategies. The result of the sum of the strengths possessed is 18.52 while the weaknesses are 9.24, so the internal factors quadrant is 18.52– 9.24 = 9.28 meaning that marketing white water nature tourism Lebong Regency exploits strengths and minimizes weaknesses contained internally. The opportunities that this strategy has are 17.60 and the threats are 9.70. So the external quadrant of factors is 17.60 – 9.70 = 7.90 which means high ability to market white water tourism Lebong Regency takes advantage of opportunities and overcomes threats faced by companies in marketing white water tourism .